2010
DOI: 10.1007/s13167-010-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vein occlusions: The potential impact of a dysregulation of the retinal veins

Abstract: A retinal vein occlusion (RVO) is a sight threatening disease. It can be divided into central vein occlusion and branch retinal vein occlusion. The pathogenesis of the condition remains to be solved. Mechanical compression of the vessel wall or thrombotic occlusion of the vessel lumen, sometimes combined with rheological disorders, are often assumed pathomechanisms. Accordingly, the therapy relies either on mechanical decompression, lyses of thrombi or improvement of rheology. A number of observations however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 74 publications
1
73
1
4
Order By: Relevance
“…FS influences the regulation of retinal venous pressure [9] that is well described for the glaucoma pathology [10]. FS has been functionally linked to the retinal vein occlusion [11]. FS plays a role in the pathology of retinitis pigmentosa [12].…”
Section: Flammer Syndrome Diagnostic Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…FS influences the regulation of retinal venous pressure [9] that is well described for the glaucoma pathology [10]. FS has been functionally linked to the retinal vein occlusion [11]. FS plays a role in the pathology of retinitis pigmentosa [12].…”
Section: Flammer Syndrome Diagnostic Approachmentioning
confidence: 97%
“…All individual parameters (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), the prevalence of which has been evaluated in the study, are functionally well linked to each other and altogether demonstrate systemic alterations of the affected person. Although individual BC subtypes differ from each other in the prevalence distribution, all of them demonstrate systemic alterations compared to the diseasefree individuals.…”
Section: Breast Cancer Is a Systemic Diseasementioning
confidence: 99%
“…Of interest were findings of increased RVP in the two extremes of the population spectrum, namely people with MetS as well as those healthy people with the Flammer syndrome (commonly slim, cold hands and feet, and arterial hypotension) [2,28]. A number of mechanisms leading to increased retinal venous pressure have previously been discussed [29].…”
Section: Discussionmentioning
confidence: 99%
“…Increased rigidity of the crossing artery induced by arteriolar sclerosis may increase the risk of occlusion. Studies investigating the vulnerebility of A/V crossing sites to BRVO have reported focal thickening of the venous basement membrane and hyperplasia of extracellular matrix and adventitia at A/V crossings [15][16][17][18][19] .…”
Section: Referencesmentioning
confidence: 99%
“…Atherosclerotic arteries may be producing increased endothelin-1 (ET-1), which may diffuse across to the neighboring vein, stimulating venous vasoconstriction [19] and increase retinal venous pressure [20] . While vascular endothelial cells produce ET-1 under a physiological condition but also all cells under stress produce ET-1.…”
Section: Referencesmentioning
confidence: 99%